The Human Immune Response to Cadaveric and Living Donor Liver Allografts - Hann, Angus; Osei-Bordom, Daniel-Clement; Neil, Desley A. H.; Ronca, Vincenzo; Warner, Suz; Perera, M. Thamara P. R. (Frontiers in Immunology, 2020)
The liver is an important contributor to the human immune system and it plays a pivotal role in the creation of both immunoreactive and tolerogenic conditions. Liver transplantation provides the best chance of survival for both children and adults with liver failure or cancer. With current demand exceeding the number of transplantable livers from donors following brain death, improved knowledge, technical advances and the desire to prevent avoidable deaths has led to the transplantation of organs from living, ABO incompatible, cardiac death donors and machine based organ preservation with acceptable results. The liver graft is the most well tolerated, from an immunological perspective, of solid organ transplants but lifelong immunosuppression is required for most recipients. Evidence suggests successful cessation of immunosuppression is possible in approximately 20-40% of liver recipients without immune mediated graft injury. The liver allograft interacts with the systemic immune system, resulting in a tolerogenic effect on the body. There is growing interest in therapies that enhances this response to achieve a state known as ‘operational tolerance’. An immunosuppression free future following liver transplantation is an ambitious but perhaps not unachievable goal. The initial immune response following transplantation is a sterile inflammatory process mediated by the innate system and the mechanisms relate to the preservation-reperfusion process. The severity of this injury is influenced by graft factors and can have significant consequences. Apart from ABOi transplants, hyperacute rejection is rare following liver transplant. Modern immunosuppressive regimes with calcineurin inhibitors improve patient and graft survival but significant side effects include renal toxicity, metabolic disturbances, infection, malignancy and the rare but life-threatening risk of PRES (posterior reversible encephalopathy syndrome). The variation of liver graft types and the different physiological responses elicited may have implications for tolerance inducing therapies. This review will outline the current understanding of the immune response towards liver allografts and highlight the areas of this topic yet to be fully understood.